Application of hydrolytic kinetic resolution (HKR) in the synthesis of bioactive compounds - Kumar, Pradeep; Naidu, Vasudeva; Gupta, Priti (Tetrahedron, 2007)
Keywords: Biological activity; bis-epoxides; Hydrolytic kinetic resolution; meso-epoxides; Natural products; synthesis; terminal epoxides

Formal synthesis of herbarumin III - Gupta, Priti; Kumar, Pradeep (Tetrahedron-Asymmetry, 2007)
An enantioselective synthesis of herbarumin III is described employing Jacobsen's hydrolytic kinetic resolution and Sharpless asymmetric dihydroxylation as the key steps. (c) 2007 Published by Elsevier Ltd.
Keywords: carboxymethyl-cellulase; F. moniliforme; pectate lyase; plant pathogenesis; polygalacturonase; Xylanase

Enantioselective synthesis of decarestrictine J - Chowdhury, Partha Sarathi; Gupta, Priti; Kumar, Pradeep (Tetrahedron Letters, 2009)
An efficient total synthesis of decarestrictine J has been achieved using ring-closing metathesis and Yamaguchi esterification as key steps. The stereogenic centres were generated by means of iterative hydrolytic kinetic resolution (HKR) of racemic epoxides. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Decanolides; epoxides; Hydrolytic kinetic resolution; Ring-closing metathesis; Yamaguchi esterification

First asymmetric total synthesis of aspinolide A - Chowdhury, Partha Sarathi; Gupta, Priti; Kumar, Pradeep (Tetrahedron Letters, 2009)
The first total synthesis of aspinolide A has been achieved using ring-closing metathesis as a key step. The stereogenic centers were generated by means of hydrolytic kinetic resolution (HKR) of racemic epoxides. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Decanolides; epoxides; Hydrolytic kinetic resolution; Ring-closing metathesis

Hydrolytic kinetic resolution as an emerging tool in the synthesis of bioactive molecules - Kumar, Pradeep; Gupta, Priti (Synlett, 2009)
A variety of racemic epoxides mainly derived from terminal olefins, such as aliphatic epoxides, multifuncitonalized epoxides and amine-substituted epoxides, have been successfully resolved into the enantiomerically pure epoxides and diols using Jacobsen's hydrolytic kinetic resolution (HKR) method. The chiral epoxides thus prepared were further elaborated by synthetic manipulation to provide a variety Of Compounds of biological interest. A general synthetic strategy for the construction Of S synlanti-1,3-polyol systems using iterative HKR has been developed, which was subsequently utilized in the synthesis of natural products with a broad range of biological activity. The protocol for the 1,3-polyols was also further extended to the synthesis of 1,3-amino alcohols.
Keywords: Biological activity; Hydrolytic kinetic resolution; Natural products; synthesis; terminal epoxides

Enantio- and diastereocontrolled total synthesis of (+)-strictifolione - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Naidu, S. Vasudeva; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2010)
A concise and practical enantioselective synthesis of (+)-strictifolione has been achieved in high diastereomeric excess using Jacobsen's hydrolytic kinetic resolution, proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde and cross olefin/ring-closing metathesis as the key steps.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; lactones; Natural products; organocatalysis; Ring-closing metathesis; Total synthesis

Organocatalytic route to the synthesis of lactone moiety of compactin and mevinolin - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Tetrahedron Letters, 2010)
An efficient synthesis of lactone moiety of compactin has been achieved. The stereogenic centers were generated by means of iterative proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Aminoxylation; Compactin; Lactone; organocatalysis; Proline

Stereoselective synthesis of ophiocerins A and C - Show, Krishanu; Gupta, Priti; Kumar, Pradeep (Tetrahedron-Asymmetry, 2011)
An efficient synthesis of ophiocerins A and C has been achieved via a common intermediate. The stereogenic centers were generated by means of Jacobsen's hydrolytic kinetic resolution and Sharpless kinetic resolution. (C) 2011 Elsevier Ltd. All rights reserved.

Organocatalytic stereoselective synthesis of passifloricin A - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2012)
The enantioselective synthesis of passifloricin A has been achieved in high diastereomeric excess. The 1,3-polyol moiety was constructed by iterative proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes while the synthesis of lactone moiety was achieved by ring-closing metathesis (RCM).

Retraction: organocatalytic stereoselective synthesis of passifloricin A (Retraction of Vol 10, Pg 1820, 2012) - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2019)